(untitled) (Gestão & Regionalidade, 2017)
This paper examines to what extent the use of section A data within the Basic Health Information System (BHIS) can contribute to the identification and mapping of housing deficiencies in small municipalities. With this purpose, this paper analyses the data from the BHIS system in the municipalities that used this source of information in order to support the elaboration of their local low-income housing plans. A case study on the municipality of Água Fria is presented, which is located in the region of Identidade Portal do Sertão in the state of Bahia, Brazil. In spite of the fact that section A data do not represent a specific information base for housing management, it may well prove to be an important instrument to identify and characterize, in a preliminary manner, housing deficiencies, while also allowing spatial mapping and the identification of several dimensions of the housing deficit. This is particularly relevant in the context of small municipalities with limited administrative capacity. However, the study provides evidence of the principle limitations of the system in terms of its impossibility to identify all the dimensions of the housing deficit and inadequacy as well as the difficulty of delineating the perimeter of the area that is covered by community health officers through adequate geographic mapping systems.